Implementasi Strategi Pembelajaran Akidah Akhlak dalam Menumbuhkan Sikap Disiplin dan Tanggung Jawab Siswa - Azqya Inayah; Andi Alifah Nurul Fathiyah; Amrin Mustofa (An-Nuha, 2026)
Moral degradation and disciplinary crises in the digital era pose serious challenges to Islamic education. This study aims to analyze the implementation of Akidah Akhlak learning strategies in fostering students' discipline and responsibility at MI Ibnu Umar Balikpapan and Sekolah Tahfidz Al Hikmah Batam. The research uses a qualitative approach with a comparative case study design. Data were collected through participant observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results show that MI Ibnu Umar Balikpapan applies a pragmatic-applicative approach through routine behavior habituation and daily religious activities. Meanwhile, Sekolah Tahfidz Al Hikmah Batam employs a spiritual-transformative approach emphasizing teacher role modeling and Qur'anic value reflection. Key success factors include teacher role modeling (uswah hasanah), a religious school culture, and consistent habituation. This study concludes that integrative Akidah Akhlak learning strategies effectively enhance students' intrinsic motivation for discipline and responsibility. Synergy between schools and parents is crucial in maintaining character consistency.